Cris rituels, auloi et tambourins : Paysage sonore et identités dans les Bacchantes d'Euripide - Christodoulou, Georgios (Synthesis.)
The text of Euripides' Bacchae mentions several times ritual shouts, auloí and drums. The theater play thus creates a fictitious sound universe, a fabric of auditory references that overlaps with the music actually perceived by the audience, in the context of the first performance at the Dionysia in Athens. Our study articulates these two sonorous spaces, by analyzing in particular the role of the aulós. This instrument indeed presents an apparent contradiction: it is what gives rhythm and melody to the Athenian festival, but it is also one of the emblems of the foreign cult. We show how the configuration of the sounds in the Bacchae multiplies the sound references, and creates a soundscape where identities are mediated and reconciled.